Efeitos de interface em bicamadas magnéticas - Rebouças, Gustavo de Oliveira Gurgel (2006)
We study magnetic interface roughness in F/AF bilayers. Two kinds of roughness were considered. The first one consists of isolated defects that divide the substrate in two regions, each one with an AF sub-lattice. The interface exchange coupling is considered uniform and presents a sudden change in the defects line, favoring Neel wall nucleation. Our results show the interface field dependence of the threshold thickness for the reorientation of the magnetization in the ferromagnetic film. Angular profiles show the relaxation of the magnetization, from Neel wall, at the interface, to reoriented state, at the surface. External magnetic field, perpendicular to the easy axis of the substrate, favors the reoriented state. Depending, of the external magnetic field intensity, parallel to the easy axis of the AF, the magnetization profile at surface can be parallel or perpendicular to the field direction. The second one treats of distributed deffects, periodically. The shape hysteresis curves, exchange bias and coercivity were characterized by interface field intensity and roughness pattern. Our results show that dipolar effects decrease the exchange bias and coercivity